Effects of geometric parameters of rectangular cooling channel on pyrolysis carbon deposition in fuel‐cooled plates. (23rd June 2021) - Huang, Qin; Chen, Yu; Bao, Zewei; Zhu, Quan; Wang, Jianli
Abstract: In this paper, the effects of the geometric parameters of a rectangular cooling channel on the amount of pyrolysis carbon deposition in the channel unit of real fuel‐cooled plates under the constraints of fixed overall plate shape and total flow rate are studied. A decoupling algorithm for simulating the carbon deposition on surfaces of three‐dimensional (3D) channels is firstly established, and a carbon deposition rate model is extended for 3D channels. Using the developed method, the processes of pyrolysis carbon deposition in five fuel‐cooled plates with various channel parameters are simulated. The effects of structural parameters on heat transfer, pyrolysis reaction, distribution of carbon deposition, and total carbon deposition amount are discussed. The results show that the channel geometric parameters indirectly affect pyrolysis carbon deposition in two ways: by changing the wall temperature where the carbon deposition reaction occurs through affecting the heat transfer and by changing the concentration of precursors through changing the residence time of fuel. A parameter θ related to the rectangular channel structure and the number of channels is defined. Under the geometric constraints of the channel unit, the smaller design parameter θ is beneficial to reduce carbon deposition in the channel.